Pengenalan Bentuk Geometri bagi Anak Usia Dini dan Sekolah Dasar Kelas Rendah Melalui Origami - Silfanus Jelatu; Maria Lim; Maria Yasinta Ngoe (Universitas Mathla'ul Anwar Banten, 2019)
INTRODUCTION TO THE GEOMETRY FORM OF EARLY AGE CHILDREN AND LOW-CLASS SCHOOL THROUGH ORIGAMI. Geometry is one of the subjects of mathematics taught from elementary school to the upper secondary level and continued in college. Geometry is also a mathematical subject that has a relationship with the real world or the world that is close to students. Introducing geometry to children is not necessary when children are in formal education, but they can get closer to geometry early. Limitation of geometry that can be given to early childhood is only on form recognition. The process is different, namely by entering the world of children or the world of the play. One that is relevant to accommodating this process is origami. Therefore, the purpose of this community service activity is to introduce geometric forms to early childhood through the game of origami. This activity was carried out in the village of Urang, Kec. Melak Kab. Manggarai NTT. The method used in this PKM activity is training that begins with a presentation. The results obtained from this activity indicate a change in choosing a game, as well as the existence of basic geometric abilities that can recognize geometric shape objects.